HYPERPROLACTINEMIA AS AN INDEPENDENT FACTOR OF INSULIN RESISTANCE - Qurbonov, D.B.; Ismoilova , S.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Hyperprolactinemia is a common endocrine pathology characterized by chronically elevated prolactin levels in the blood and is now increasingly recognized as an independent factor in the development of insulin resistance. This review analyzes data from recent studies on the impact of hyperprolactinemia on carbohydrate and lipid metabolism and examines potential mechanisms of insulin resistance formation in the absence of classical metabolic disorders. Special attention is given to the direct effects of prolactin on body weight, lipid profile, glucose homeostasis, and insulin secretion. Clinical research results are presented, confirming the presence of insulin resistance in patients with hyperprolactinemia, even with normal body weight and in the absence of overt inflammatory syndrome. The role of prolactin as a potential marker of primary insulin resistance and its significance in the differential diagnosis of metabolic disorders are substantiated.